A Novel Microviridae Phage (CLasMV1) From “Candidatus Liberibacter asiaticus” - Zhang, Ling; Li, Ziyi; Bao, Minli; Li, Tao; Fang, Fang; Zheng, Yongqin; Liu, Yaoxin; Xu, Meirong; Chen, Jianchi; Deng, Xiaoling; Zheng, Zheng (Frontiers in Microbiology, 2021)
“Candidatus Liberibacter asiaticus” (CLas) is an unculturable phloem-limited α-proteobacterium associated with citrus Huanglongbing (HLB; yellow shoot disease). HLB is currently threatening citrus production worldwide. Understanding the CLas biology is critical for HLB management. In this study, a novel single-stranded DNA (ssDNA) phage, CLasMV1, was identified in a CLas strain GDHZ11 from Guangdong Province of China through a metagenomic analysis. The CLasMV1 phage had a circular genome of 8,869 bp with eight open reading frames (ORFs). While six ORFs remain uncharacterized, ORF6 encoded a replication initiation protein (RIP), and ORF8 encoded a major capsid protein (MCP). Based on BLASTp search against GenBank database, amino acid sequences of both MCP and RIP shared similarities (coverage > 50% and identity > 25%) to those of phages in Microviridae, an ssDNA phage family. Phylogenetic analysis revealed that CLasMV1 MCP and RIP sequences were clustered with genes from CLas and “Ca. L. solanacearum” (CLso) genomes and formed a unique phylogenetic lineage, designated as a new subfamily Libervirinae, distinct to other members in Microviridae family. No complete integration form but partial sequence (∼1.9 kb) of CLasMV1 was found in the chromosome of strain GDHZ11. Read-mapping analyses on additional 15 HiSeq data sets of CLas strains showed that eight strains harbored complete CLasMV1 sequence with variations in single-nucleotide polymorphisms (SNPs) and small sequence insertions/deletions (In/Dels). PCR tests using CLasMV1-specific primer sets detected CLasMV1 in 577 out of 1,006 CLas strains (57%) from southern China. This is the first report of Microviridae phage associated with CLas, which expands our understanding of phage diversity in CLas and facilitates current research in HLB.